Religious Learning Using The Sing A Song Method At The Sungai Buloh Guidance Center, Kuala Lumpur - Fanreza Robie; Nurman Ginting; Arwin Juli Rakhmadi; Riyan Pradesyah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Based on the results of observations and preliminary studies, it was found that students' ability to understand religious subjects at the Sungai Buloh Guidance Studio, Kuala Lumpur, was still low, this was evidenced by the process and learning outcomes. This activity is usually held once a week at the Sungai Buloh Guidance Studio. In the activity of conveying religious learning material, there were educators who delivered religious subjects using non-cooperative methods. It was found that when students received religious subject matter, there was a delay. Then there has been no maximum effort to use the cooperative method to increase students' understanding of religious subject matter by educators. The solution offered to the Sungai Buloh Guidance Center is to provide training to educators using the Sing A Song Method in delivering religious subject matter to students. The Sing A Song method is a way of teaching and introducing religious subject matter with a singing method that uses certain lyrics that are sung. Usually the lyrics of the songs are adjusted to the subject matter that will be taught to students which is done repeatedly in this training. Initially, educators were given the opportunity to make song lyrics adapted to the subject matter and then also adapted to the tunes of songs that were easy for students to memorize. Then educators practice how to deliver and teach directly to students, and later will be accompanied by mentors provided. After that an evaluation was carried out, by means of which the participants read one verse of the Koran, so that they could find out the level of understanding that had been achieved.